Pernikahan Sedarah dalam Perspektif Islam dan Genetika - Rahayu Dwi Lestari (Universitas Islam Malang, 2022)
Inbreeding marriage or also called same-sex marriage is a marriage carried out between a woman and a man who still has a very close blood relationship. Allah SWT. forbids marrying women who are related, mahram, whether by lineage, breast milk or semenda. This prohibition is permanent, at any time and in any situation. From a legal perspective, incestuous marriage is a legal marriage, but once it is known, the marriage is null and void by law. Incest marriage, regardless of the circumstances, if it is done intentionally, the law is unlawful. Inbreeding can cause a decrease in the quality of the offspring produced. Inbreeding greatly affects the gene composition of the offspring produced. The possibility of the appearance of a homozygous fraction will increase. In humans, having a homozygous recessive gene causes many genetic disorders, sometimes even fatal (death). The wisdom behind the prohibition of inbreeding is to maintain the honor of oneself and one's family, and that is to prevent damage and negative effects that can appear on generations of offspring.